Analisis Teknologi Bersih dan Minimasi Limbah pada Industri Tahu Rumahan Kota Pontianak (Analysis of Clean Technology and Minimization of Waste in the Home-based Tofu Industry on Jl. Parit Pangeran, Pontianak City, West Kalimantan) - Khairunnissa, Rizqa; Nissa, Hairun; Banun, Emylyana Maylany; Apriani, Isna; Jati, Dian Rahayu (Universitas Tanjungpura, 2020)
Abstract The home industry is currently growing rapidly, not inferior to large industries. One of the fastest growing industries is the tofu industry. Tofu industry which is located on Jl. Parit Pangeran, Pontianak City, can produce tofu ranging from 1004 to 1005 grains which are distributed to the Flamboyan Market. This soy-based food is in great demand by the public, apart from its taste, the protein content in tofu is also good for the human body. The tofu production process includes soaking 500 kg of soybeans, milling, pressing, cooking, freezing, and printing. In each production process, tofu will produce output in the form of semi-finished products or waste. The results of the analysis of the application of clean production and waste minimization in the tofu industry are the addition of SOPs, goodhouse keeping, recycle, fuel replacement, extension of water life, use of blowers in the cooking process, reuse of cooking water, utilization of ash waste, and manufacture of liquid fertilizer. Keywords: Production and Waste Minimization, Tofu Industry, Quick Scanning Abstrak Industri rumahan saat ini berkembang pesat tak kalah dengan industri besar. Salah satu industri yang berkembang pesat adalah industri tahu. Industri tahu yang terletak di Jl. Parit Pangeran, Kota Pontianak, dapat menghasilkan tahu berkisar 1004 hingga 1005 butir yang didistribusikan ke Pasar Flamboyan. Makanan berbahan dasar kedelai ini banyak diminati oleh masyarakat, selain karena rasa, kandungan protein pada tahu juga baik bagi tubuh manusia. Proses produksi tahu ini meliputi perendaman kedelai sebanyak 500 kg, penggilingan, pemerasan, pemasakan, pembekuan, dan pencetakan. Pada tiap proses produksi tahu akan menghasilkan output berupa produk setengah jadi, maupun limbah. Hasil analisis penerapan produksi bersih dan minimasi limbah di industri tahu ini yang bisa disarankan adalah penambahan SOP, good housekeeping, recycle, penggantian bahan bakar, perpanjangan masa pakai air, penggunaan blower pada proses pemasakan, reuse air saat proses memasak, pemanfaatan limbah abu, dan pembuatan pupuk cair. Kata Kunci: Produksi Bersih dan Minimasi Limbah, Industri Tahu, Quick Scanning